STRUKTUR KEPEMILIKAN, KOMITE AUDIT, DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi pada sektor Agriculture yang Listing di BEI periode 2013-2017) - MAZIYYATUR ROHMAH, ISNAINI (Jurnal Ilmu Manajemen (JIM), 2019)
This purpose of the research was to analyze the influence of ownership structure, audit committee, andcompany characteristics on the firm value. The type of data used in this research was quantitative data sourcedfrom secondary data. The sampling technique used was purposive sampling and obtained 8 companies with 40sample unit from the object of research agriculture sector listed on the Stock Exchange for the period 2013-2017. The data analysis technique used was multiple linear regression. The results showed that firm size andleverage have positive and significant effect on firm value. However, in managerial ownership variables,institutional ownership, audit committee, company performance, and liquidity there is no significant effect onfirm value. This shows that companies do not need to increase or decrease the percentage of independentvariables that have no influence on the dependent variable. Conversely, companies need to increase thepercentage of 2 variables such as firm size and leverage because there is a positive and significant effect onfirm value. The added value of assets will have signal for investors to invest because it was considered to be ingood condition, with the value of the company increasing. And the addition of leverage can be also function toincrease the value of the company or at least able to minimize the cost of capital if the company is able to takeadvantage of the existence of the taxes.Keywords: audit committee; company characteristics; companys ownership; PBV.